Fear to fail and entrepreneurship intent: Examining linkages and potential pathways in Senegal - Cheikh T. Ndour; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
This study aims to investigate the effect of fear of failure on entrepreneurship intent. It utilises survey data from the Global Entrepreneurship Monitor (2015) conducted in Senegal. Analysing a sample of 2364 individuals, the probit model was employed, revealing three key findings. Firstly, fear of failure significantly diminishes entrepreneurship intent. Secondly, individuals who are partially employed demonstrate a heightened inclination towards entrepreneurship. Thirdly, fear of failure consistently impacts entrepreneurship intent regardless of gender. A key policy implication of this research is the necessity to address discrimination in policies designed to support individuals with greater entrepreneurial aspirations.
Keywords: L26; J29; J16; C25; O55; 330; Entrepreneurship intent; probit; occupation; gender; Senegal